Characterization of S-adenosylhomocysteine/Methylthioadenosine nucleosidase on secretion of AI-2 and biofilm formation of Escherichia coli. (July 2017) - Han, Tian; Li, Yanhua; Shan, Qiuli; Liang, Wenjing; Hao, Weiwei; Li, Yumei; Tan, Xiaojun; Gu, Jinsong
Abstract: S -adenosylhomocysteine/Methylthioadenosine nucleosidase (SAHN E.C.3.2.2.9) does not exist in mammalian cells but is essential for methyl recycling in numerous bacterial and protozoan species. Inhibition of this enzyme could limit synthesis of autoinducers of bacterial quorum sensing (QS), and hence, causes reduction in biofilm formation and may attenuate virulence. In this study, sahn deletion mutant of E. coli MG1655, sahn -complemented strain, and SANH-overexpressing strain were established and used to identify the secretion of autoinducer-2 (AI-2) and biofilm formation. The results indicated that deletion of the sahn gene abolished the production of the QS signal AI-2 and biofilm formation in mutant strain MG1655-Δ sahn . And the complementation strain MG1655-Δ sahn (pET-28a- sahn ) showed restored production of AI-2 and biofilm formation, which indicates that the sahn gene plays an important role in bacterial quorum sensing. The recombinant SAHN protein was overexpressed and purified. The enzymatic activity of SAHN was successfully determined by a coupling-enzyme analysis based on xanthine oxidase, with the V max and K m of SAHN enzymatic reaction confirmed. Given that sahn is essential for the quorum sensing of both Gram-negative and Gram-positive bacteria, SAHN could be a potential target for wide-spectrum antibiotics. Highlights: A sahn deletion mutant of was constructed with Red/ET recombination system. A sahn -complemented strain and a SANH-overexpressing strain were also established. Secretion of QS signal AI-2 and biofilm formation in mutant strains were identified. Recombinant SAHN protein was overexpressed and purified. Enzymatic activity of SAHN was determined with a coupled-enzyme assay.